2010
DOI: 10.3892/ijo_00000760
|View full text |Cite
|
Sign up to set email alerts
|

Critical involvement of RQCD1 in the EGFR-Akt pathway in mammary carcinogenesis

Abstract: Abstract. We previously reported an important role of RQCD1 in mammary carcinogenesis through the interaction with Grb10 interacting GYF protein 1 (GIGYF1), Grb10 interacting GYF protein 2 (GIGYF2) and growth factor receptor binding protein 10 (Grb10). In this study, we investigated the biological mechanism of RQCD1 in regulation of the Akt activity as the downstream signal of epidermal growth factor receptor (EGFR). Knockdown of RQCD1 reduced the Akt phosphorylation level that was induced by epidermal growth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Short hairpin RNA (shRNA)-mediated suppression of CNOT9 drastically suppresses the proliferation of breast cancer cells (Ajiro et al, 2009). In addition, CNOT9 forms a large complex consisting of Grb10, Grb10-interacting protein 1 (GIGYF1), GIGYF2, and Akt, all of which are components of epidermal growth factor receptor (EGFR) downstream signaling (Ajiro et al, 2010). The Akt phosphorylation that is induced by EGFR signaling is attenuated in the absence of CNOT9 (Ajiro et al, 2010), which suggests that CNOT9 enhances EGFR signaling and contributes to carcinogenesis and progression of cancer, particularly in mammary glands.…”
Section: Cnot9mentioning
confidence: 99%
“…Short hairpin RNA (shRNA)-mediated suppression of CNOT9 drastically suppresses the proliferation of breast cancer cells (Ajiro et al, 2009). In addition, CNOT9 forms a large complex consisting of Grb10, Grb10-interacting protein 1 (GIGYF1), GIGYF2, and Akt, all of which are components of epidermal growth factor receptor (EGFR) downstream signaling (Ajiro et al, 2010). The Akt phosphorylation that is induced by EGFR signaling is attenuated in the absence of CNOT9 (Ajiro et al, 2010), which suggests that CNOT9 enhances EGFR signaling and contributes to carcinogenesis and progression of cancer, particularly in mammary glands.…”
Section: Cnot9mentioning
confidence: 99%
“…However, all the DE genes within our "B-other" group differed from class-defining genes of the so called "novel" ALL subtype introduced by Yeoh et al (3) implying that they specify a different subtype. Each validated gene in this category, i.e., CD3G, DFFA, GIGYF1, GIGYF2, and INTS3 were shown to play a role in neoplastic processes, including leukemia (41)(42)(43)(44)(45). However, none of these genes were published previously to be associated with pediatric BCP-ALL.…”
Section: Discussionmentioning
confidence: 97%
“…The functional oncogenic role of CNOT9/RQCD1 in melanoma remains currently unknown although limited studies revealed RQCD1 implication in AKT activation and cell proliferation (Ajiro et al, 2009(Ajiro et al, , 2010. In particular, the CNOT9/RQCD1 mutant has demonstrated to stimulate stronger immune responses than the wild type, implicating the formation of a neoantigen that could be a potential therapeutic target although no drugs or clinical trials are available (Wong et al, 2015).…”
Section: Cnot9mentioning
confidence: 99%